Delimiting the Function of the C-Terminal Extension of the Escherichia coli [NiFe]-Hydrogenase 2 Large Subunit Precursor - Pinske, Constanze; Thomas, Claudia; Nutschan, Kerstin; Sawers, R. Gary (Frontiers in Microbiology, 2019)
The active site of all NiFe-hydrogenases (Hyd) has a bimetallic NiFe(CN)2CO cofactor that requires the combined action of several maturation proteins for its biosynthesis and insertion into the precursor form of the large subunit of the enzyme. Cofactor insertion is an intricately controlled process and the large subunit of almost all Hyd enzymes has a C-terminal oligopeptide extension that is endoproteolytically removed as the final maturation step. This extension serves either as a recognition and interaction platform for the maturation proteins, or it has a structural role in ensuring the active site cavity remains open until the cofactor is inserted. To distinguish between these alternatives, we exchanged the complete C-terminal extension of the precursor of Escherichia coli hydrogenase 2 (Hyd-2) for the C-terminal extension of the Hyd-1 enzyme. Using in-gel activity staining, we demonstrate clearly that this large subunit precursor retains its specificity for the HybG maturation chaperone, as well as for the pro-HybC-specific endoprotease HybD, despite the C-terminal exchange. Bacterial two-hybrid studies confirmed interaction between HybD and the pro-HybC variant carrying the exchanged C-terminus. Limited proteolysis studies of purified precursor and mature HybC protein revealed that, in contrast to the precursor, the mature protein was protected against trypsin attack, signifying a major conformation change in the protein. Together, our results support a model whereby the function of the C-terminal extension during subunit maturation is structural.